Dishevelled and Wnt signaling: is the nucleus the final frontier? - Habas, Raymond (BioMed Central, 2005)
The phosphoprotein Dishevelled (Dsh) is an essential component of Wnt signaling pathways and transduces signals into three separate branches, the canonical, non-canonical and Ca(2+ )pathways. How Dsh focuses signaling into these branches remains mysterious, but a new study reveals the importance of nuclear localization of Dsh for pathway-specific activation.